2011
DOI: 10.1017/s1740925x12000130
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glutathione S-transferase genes polymorphisms and the risk of schizophrenia in a sample of Iranian population

Abstract: Glutathione S-transferases (GSTs) are major intracellular antioxidants, which, impaired in their function, are involved in the progress of schizophrenia (SCZ). The aim of this case-control study was to investigate the association between the polymorphism of glutathione S-transferases M1 (GSTM1), T1 (GSTT1), the glutathione S-transferase P1 gene (GSTP1) and SCZ. We isolated genomic DNA from peripheral blood of 93 individuals with SCZ and 99 healthy control subjects' genotypes analyzing them for GSTM1, GSTT1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Previous studies reported that the frequencies of these genetic variants vary among human ethnic groups. 26 The genotype distribution of these variants in the Chinese population is similar to that of the Korean and Japanese populations but different from European, South American, and African populations. 27 Common homozygous deletion polymorphisms of the GSTT1 and GSTM1 genes, as well as the GSTP1 Ile105 SNP, have been shown to eliminate enzyme activity and increase susceptibility to oxidative stress.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Previous studies reported that the frequencies of these genetic variants vary among human ethnic groups. 26 The genotype distribution of these variants in the Chinese population is similar to that of the Korean and Japanese populations but different from European, South American, and African populations. 27 Common homozygous deletion polymorphisms of the GSTT1 and GSTM1 genes, as well as the GSTP1 Ile105 SNP, have been shown to eliminate enzyme activity and increase susceptibility to oxidative stress.…”
Section: Introductionmentioning
confidence: 75%
“…These findings also suggest that the GSTP1 polymorphism may not increase the susceptibility to SCZ in Koreans; 28 however, they did not completely rule it out, as other studies have concluded that GSTP1 (rs1695 AG, AG+GG) does increase the risk of SCZ in Koreans. 26 Schizophrenia is related to oxidative stress. Many studies found that the level of oxidative stress was different between men and women, mainly manifested by higher levels of oxidative stress in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that environmental exposure and genetic factors increase the risk of schizophrenia and other psychotic disorders [18]. Furthermore, some studies have suggested that the combination of various GST polymorphisms may make an individual susceptible to schizophrenia by affecting the capacity of the cells to detoxify the oxidized metabolites of catecholamines [13,19]. Nevertheless, epigenetic studies might shed light on the various non-Mendelian irregularities of schizophrenia and help solve many issues that cannot be examined by DNA sequence-based technology [20].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the studied population had been previously published [12,13]. The Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) guidelines were applied for the diagnosis of patients.…”
Section: Methodsmentioning
confidence: 99%